Lidová píseň v hudební výchově na základních a středních školách v České republice - Kučerová, Judita (Masaryk University Press, 2019)
Title in English: Folk Song in Music Education at Primary and Secondary Schools in the Czech Republic The monograph presents and reflects the results of a specific research project of the same name (MUNI/A/1423/2018) carried out by a team of academic staff and students of the doctoral program of the Department of Music at the Faculty of Education, Masaryk University. The folklore song scope represents an important didactic basis, permeates music education at elementary, partly also secondary schools and specialized instrumental or singing education at elementary art schools. Due to the influence of multilayered cultural expressions and the influence of multimedia means, however, the question of how to present the musical and folklore heritage to school youth is more prominent. The object of investigation was the application of folk music to school education.